2022
DOI: 10.21203/rs.3.rs-1789926/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neopestalotiopsis australis Causing Scab Disease on Byrsonima crassifolia in Mexico.

Abstract: Nanche (Byrsonima crassifolia) has great economic importance in the dry and humid tropics in Mexico, where is used for the elaboration of different drinks, foods, and candies; also in the traditional medicine to treat fever and stomach disorders. Since 2021, a high incidence of disease-causing scabby fruit in young nanche fruits has been detected in Las Choapas, Veracruz, Mexico. Disease symptoms were visible on the skin of fruits which progressed as fruits matured. Therefore, the objectives of this study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Therefore, more information on the pests that can cause production losses is required. For example, Moreno-Velázquez et al (2022) Similarly, Sousa et al (2021) reported that flies (Diptera: Lonchaeidae) attack fruits and flower buds. For instance, Bactrocera carambolae, the carambola fruit fly, is a B. crassifolia pest (Jesus-Barroos et al, 2015).…”
Section: Pests and Diseasesmentioning
confidence: 99%
“…Therefore, more information on the pests that can cause production losses is required. For example, Moreno-Velázquez et al (2022) Similarly, Sousa et al (2021) reported that flies (Diptera: Lonchaeidae) attack fruits and flower buds. For instance, Bactrocera carambolae, the carambola fruit fly, is a B. crassifolia pest (Jesus-Barroos et al, 2015).…”
Section: Pests and Diseasesmentioning
confidence: 99%